A Process for the Design and Development of Novel Bone Morphogenetic Protein-7 (BMP-7) Mimetics With an Example: THR-184 - Carlson, William D.; Keck, Peter C.; Bosukonda, Dattatreyamurty; Carlson, Frederic Roy (Frontiers in Pharmacology, 2022)
Growth Factors have been evaluated as therapeutic targets for the treatment of a broad spectrum of diseases. Because they are proteins with pleiotropic effects, the quest to harness their beneficial effects has presented challenges. Most Growth Factors operate at the extracellular-receptor level and have natural feedback mechanisms that modulate their effects. As proteins, they are difficult and expensive to manufacture. Proteins must be administered parenterally, may invoke an immune response, and may be neutralized by naturally occurring inhibitors. To circumvent these limitations, the authors have undertaken an effort to develop mimetics for the Bone Morphogenetic Protein (BMP) signaling pathways that incorporate the beneficial effects, eliminate the deleterious effects, and thereby create effective drug-like compounds. To this end, the authors have designed and tested a family of small peptide BMP mimetics. The design used the three-dimensional structure of BMP-7 and an algorithm that uses experimental activity data to identify structure/activity relationships. The desired activities are then optimized based on in vitro and in vivo assays. One member of this family, THR-184, is an agonist of BMP signaling and a potent antagonist of TGFβ signaling. This small peptide mimetic inhibits inflammation, apoptosis, and fibrosis by regulating multiple signaling pathways involved in Acute Kidney Injury (AKI). THR-184 has progressed through phase I and II clinical trials for the prevention of Cardio-Vascular Surgery (CVS) associated AKI. This work provides a roadmap for the development of other growth factor mimetics and demonstrates how we might harness their therapeutic potential.